Plant genetic resources for food and agriculture: opportunities and challenges emerging from the science and information technology revolution - Halewood, Michael; Chiurugwi, T.; Sackville-Hamilton, N. Ruaraidh; Kurtz, B.; Marden, E.; Welch, Eric W.; Michiels, F.; Mozafari, J.; Sabran, M.; Patron, N.; Kersey, Paul J.; Bastow, R.; et al. (Wiley, 2018)
Over the last decade, there has been an ongoing revolution in the exploration, manipulation and synthesis of biological systems, through the development of new technologies that generate, analyse and exploit big data. Users of Plant Genetic Resources (PGR) can potentially leverage these capacities to significantly increase the efficiency and effectiveness of their efforts to conserve, discover and utilize novel qualities in PGR, and help achieve the Sustainable Development Goals (SDGs). This review advances the discussion on these emerging opportunities and discusses how taking advantage of them will require data integration and synthesis across disciplinary, organisational and international boundaries, and the formation of multi-disciplinary, international partnerships. We explore some of the institutional and policy challenges that these efforts will face, particularly how these new technologies may influence the structure and role of research for sustainable development, ownership of resources, and access and benefit sharing. We discuss potential responses to political and institutional challenges, ranging from options for enhanced structure and governance of research discovery platforms to internationally brokered benefit-sharing agreements, and identify a set of broad principles that could guide the global community as it seeks or considers solutions.